Exodus. Gods and kings [videorecording (DVD)] - Bale, Christian, 1974-; Edgerton, Joel, 1974-; Kingsley, Ben, 1943-; Turturro, John, 1957-; Weaver, Sigourney, 1949- (20th Century Fox Home Entertainment, 2015)
Moses sets out to rise up against the Egyptian Pharaoh. He frees 600,000 slaves and they all journey across Egypt fighting deadly plagues. The epic tale of one man's daring courage to take on an empire.